COMPARISON OF BOTULINUM TOXIN VS LATERAL SPHINCTEROTOMY FOR THE TREATMENT OF CHRONIC ANAL FISSURE - KHAN, A; ZARIN, M; KHADEEJA, . (Biological and Clinical Sciences Research Journal, 2024)
Chronic anal fissure is a distressing condition characterized by a tear or ulcer in the lining of the anal canal. Objectives: The primary aim of this study is to compare the effectiveness of botulinum toxin versus lateral sphincterotomy in the treatment of chronic anal fissures. Methods: This comparative study was conducted at Khyber Teaching Hospital, Peshawar, from 13th August 2023 to 3rd December 2023. Data were collected from 278 patients diagnosed with chronic anal fissure, retrospectively extracted from electronic medical records. A total of 268 patients were included in the analysis, with 134 patients in each treatment group. Baseline characteristics, including age, gender distribution, and duration of symptoms, were recorded for both groups. Results: The mean age of patients in the botulinum toxin group (Group A) was 42.5 ± 8.3 years, and in the lateral sphincterotomy group (Group B) it was 45.2 ± 7.9 years. There were 52% males in Group A and 48% in Group B. The mean duration of symptoms was 10.3 ± 4.7 months in Group A and 11.8 ± 5.2 months in Group B. Symptom resolution was significantly higher in the lateral sphincterotomy group (92%) compared to the botulinum toxin injection group (78%). Conclusion: Lateral sphincterotomy demonstrates superior efficacy in promoting symptom resolution and fissure healing compared to botulinum toxin injection, albeit with a higher risk of complications.